The descriptive epidemiology of Streptococcus pneumoniae and Haemophilus influenzae nasopharyngeal carriage in children and adults in Kilifi district, Kenya. - Abdullahi, O; Nyiro, J; Lewa, P; Slack, M; Scott, J (2008)
BACKGROUND: Transmission and nasopharyngeal colonization are necessary steps en route to invasive pneumococcal or Haemophilus influenzae disease but their patterns vary geographically. In East Africa we do not know how these pathogens are transmitted between population subgroups nor which serotypes circulate commonly. METHODS: We did 2 cross-sectional nasopharyngeal swab surveys selecting subjects randomly from a population register to estimate prevalence and risk-factors for carriage in 2004. H. influenzae type b vaccine was introduced in 2001. RESULTS: Of 450 individuals sampled in the dry season, 414 were resampled during the rainy season. Among subjects 0-4, 5-9, and 10-85 years old pneumococcal carriage prevalence was 57%, 41%, and 6.4%, respectively. H. influenzae prevalence was 26%, 24%, and 3.0%, respectively. Prevalence of H. influenzae type b in children <5 years was 1.7%. Significant risk factors for pneumococcal carriage were rainy season (odds ratio [OR]: 1.65), coryza (OR: 2.29), and coculture of noncapsulate H. influenzae (OR: 7.46). Coryza was also a risk factor for H. influenzae carriage (OR: 1.90). Of 128 H. influenzae isolates, 113 were noncapsulate. Among 279 isolates of Streptococcus pneumoniae, 40 serotypes were represented and the distribution of serotypes varied significantly with age; 7-valent vaccine-types, vaccine-related types, and nonvaccine types comprised 47%, 19%, and 34% of strains from children aged <5 years. Among older persons they comprised 25%, 28%, and 47%, respectively (P = 0.005). CONCLUSIONS: The study shows that pneumococcal carriage is common up to 9 years of age and that the majority of serotypes carried at all ages are not covered specifically by the 7-valent pneumococcal conjugate vaccine.